A Cross-Sectional Survey of Iraqi Herbalist Practicing in the Middle Euphrates Area with a Recognition of their Knowledge, Practice and Attitude(Conference Paper )# - Humadi, Suhad; Hassan, Saif M.; Ahjel , Salam W. (Iraqi Journal of Pharmaceutical Sciences, 2023)
High percentage of the Iraqi population profoundly rely on folk medicine to meet their health needs which makes their safety questionable. This study aims to evaluate Iraqi herbalists' knowledge and practice to ensure the public's safety.This study was conducted in a cross-sectional design between October 2021 and March 2022, using a pretested questionnaire administered to Iraqi herbalists practicing in Middle Euphrates Area. Through face-to-face meetings, participants completed a multicomponent questionnaire comprising 15 items in four sections. The data obtained were analyzed using a statistical package for social sciences; Chi-square was used to correlate some variables, and P-values of <0.05 were considered significant. A total of 54 male herbalists from five Iraqi provinces joined this survey, the majority practicing in Kabala. Most herbalists had 10- 20 years of experience, and more than 50% had a university degree. Data showed that 72.2% of herbalists identify their herbal items using their own experience, and 35.2% use this experience as their sole source of knowledge. Only 35.1% use herbal books in conjugation with their experiences, and a few (1.9%( use multiple sources of information. Herbalists with more years of experience (79.6%( evaluate patient conditions properly, follow up (40.7%(, and refer patients to their physicians when needed (42.6%(. Although fifty percent of herbalists educate their patients regarding the storage condition of remedies, most of them refrain from writing the complete ingredients on their final product regardless of their experience. Results also showed that most herbalists do not have a record tracking adverse reaction.Most Iraqi herbalists lack the proper system for prescribing and dispensing their remedies and adequately identifying the sold herbs. The study showed a variation in practice among herbalists using approaches based mainly on their experience.